RANCANG BANGUN MINIATUR SISTEM ALAT PENGUKUR STANDAR KEBISINGAN KNALPOT SEPEDA MOTOR BERBASIS ARDUINO UNO - Budi Santoso; Sayuti Rahman; Arnes Sembiring (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Sound is one element of the vibration of an object whare the vibration occurs around the air that propagates from all directions whare the results vary form the air pressure that applies to the surface of the eardrum that is heard, Motorcycles are vehicles that are ofthen used as transportation that is used with this transportation to make it easier for users and the sound produced from the exhaust is a noise that is often heard on the highway and there based on these problems, the authors design a miniature system for measuring standard on the entire LM 393 Sound Sensor series to measure the level of noise produced by the exhaust and OLED which serves to display sensor values. The way of application is that the system and gets information on the sound sensor value from a miniature standard exhaust noise gauge, to fine out whether the value generated by the user can see the result on the OLED screen.